Distinct effects of adjuvants on B cell responses to protein or polysaccharide antigens contained in glycoconjugate vaccines - Budroni, Sonia; Faenzi, Elisa; Tavarini, Simona; Sammicheli, Chiara; Buricchi, Francesca; Volpini, Gianfranco; Borgogni, Erica; Spensieri, Fabiana; Balducci, Evita; Galletti, Bruno; Romano, Maria Rosaria; D’Oro, Ugo; et al. (Frontiers in Immunology, 2025)
BackgroundProtein-polysaccharide conjugate vaccines rely on the induction of T-cell-dependent responses that support germinal center (GC) reactions to potentiate the expansion of antigen-specific memory B-cell (MBC) populations and high-avidity antibody responses. The effects of adjuvants on B-cell and antibody responses are well described for protein antigens but remain largely unexplored for conjugated polysaccharidic antigens.MethodsWe assessed the effects of five adjuvants present in licensed vaccines (AS01, AS03, AS04, and aluminum hydroxide [Alum]) or under clinical evaluation (AS37) on the magnitude and quality of antigen-specific antibody responses and local/systemic B-cell responses. Naive mice received three immunizations of adjuvanted or non-adjuvanted model glycoconjugate vaccine containing Staphylococcus aureus (SA) capsular polysaccharide serotypes 5/8 (CP5/8) conjugated to a tetanus toxoid carrier and inactivated SA HlaH35L toxin.ResultsAll AS-containing vaccines increased CP5/8-specific antibody titers and B-cell immunity relative to Alum- or non-adjuvanted formulations. After two immunizations, AS03 (α-tocopherol-containing oil-in-water emulsion) most robustly enhanced CP5/8-specific immunity relative to the other adjuvants or no adjuvant. AS03 induced higher responses of high-avidity antibodies persisting for at least 25 weeks post-immunization and greater expansions of populations of splenic GC B cells, mature MBCs in the lymph node or spleen, and long-lived plasma cells in the bone marrow. These effects increased with each immunization, suggesting the presence of avidity maturation and highlighting the role of the carrier in improving the quality of GC reactions. While HlaH35L-specific responses were augmented by each adjuvant, they lacked significant inter-group differences, pointing to profound differences in the adjuvants’ effects on polysaccharide vs. protein antigens in the mice of the present study.ConclusionInvestigating the antibody quantity and quality and local and systemic B-cell population expansions in a naive model supports our understanding of how different adjuvants shape the response to the tested polysaccharidic antigens.